Pengaruh Dimensi Kualitas Pelayanan Terhadap Loyalitas Penumpang Trans Padang - Aris Agung Wicaksono; Okki Trinanda (Jurnal Ecogen, 2020)
The aim of this study was to determine the impact of service quality in passenger retention in Trans Padang. These researchs were descriptive and quantitative. The study consist of residents in Padang, who frequently use the Trans Padang Pasar Raya – Lubuk Buaya route. The data used were primary and secondary data. We used questionnaires and documents. The sample of this technique was a targeted sample with a total sample size of 100 respondents. This analysis method had been use repeatedly with SPSS version 23 regrression analysis. The hypothesis study uses in this data analysis such as validation, reliability, normality, multicollinearity, heterogeneity, F-test, and T-statistic test at a = 0.05. the result of this study show that 1)Reliability had a significant negative impact on passenger loyality in Trans Padang. 2)Responsibility had a significant positive impact on the loyality of Trans Padang. 3)assurance had a significant positive impact on the loyality of Trans Padang. 4) Empathy had a significant positive impact on the loyality of Trans Padang. 5)Tangible had a significant negative impact on the loyality of Trans Padang passengers.Keywords : reliability, responsiveness, assurance, empathy, tangible and loyalty